2017
DOI: 10.1038/s41598-017-01529-2
|View full text |Cite
|
Sign up to set email alerts
|

Super-light Cu@Ni nanowires/graphene oxide composites for significantly enhanced microwave absorption performance

Abstract: Graphene oxide (GO) was rarely used as microwave absorption (MA) material due to its lower dielectric loss compared with reduced GO (RGO). However, the characteristics of low conductivity, light weight, and large surface area were beneficial to the impedance matching for absorbers already containing highly conductive metal materials. Cu@Ni nanowires are promising MA materials due to the desired dielectric loss from copper and excellent magnetic loss from nickel. However, the high density was an impediment to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(49 citation statements)
references
References 53 publications
2
47
0
Order By: Relevance
“…While the spectra of the Cu films ( Figure 6 a) were similar for all three specimens, showing a mixture of Cu and Cu 2 O; the Cu 2p peaks recorded on the glass side needed an additional peak fit analysis ( Figure 6 b), 40 showing an additional contribution of Cu(OH) 2 in the as-deposited state, which vanished in the annealed state. 41 The chemical composition is identical between both as-deposited runs. From these results, it can be demonstrated that the interface chemistry is similar for the as-deposited and annealed samples and thus does not significantly contribute to the different adhesion energies that were measured.…”
Section: Resultsmentioning
confidence: 92%
“…While the spectra of the Cu films ( Figure 6 a) were similar for all three specimens, showing a mixture of Cu and Cu 2 O; the Cu 2p peaks recorded on the glass side needed an additional peak fit analysis ( Figure 6 b), 40 showing an additional contribution of Cu(OH) 2 in the as-deposited state, which vanished in the annealed state. 41 The chemical composition is identical between both as-deposited runs. From these results, it can be demonstrated that the interface chemistry is similar for the as-deposited and annealed samples and thus does not significantly contribute to the different adhesion energies that were measured.…”
Section: Resultsmentioning
confidence: 92%
“…All these peaks are suggesting the Cu o and Cu 2+ states of Cu in CTC HLSs owing to the presence of Cu metal and Cu(OH) 2 in the final product. [ 41 ] Co 2p has been split into Co 2p 3/2 (779.94 eV) and Co 2p 1/2 (795.25 eV) (Figure 4d). The satellite peaks of Co 2p 3/2 and Co 2p 1/2 presented at 783.8 and 801.58 eV, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…However, their high cost and non-abundance in the earth are regarded as huge disadvantages in terms of their usage for the economical ERC electrode materials [26][27][28]. Recent studies have shown that non noble metals such as Cu and Zn components could be good candidates for the ERC electrode materials because of their high electrocatalytic activity and high abundance in the earth, but it still needs improvement in terms of CO selectivity [29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%